2013
DOI: 10.2298/vsp1305469s
|View full text |Cite
|
Sign up to set email alerts
|

The influence of retrobulbar adipose tissue volume upon intraocular pressure in obesity

Abstract: In obese people, elevated intraocular pressure may be caused by changes in ocular blood flow, affected by the physical pressure exerted by higher retrobulbar adiposity, and/or by internal vascular changes secondary to complications of obesity. These findings indicate the need for more frequent measurement of intraocular pressure in obese individuals to earlier detect glaucoma, and in so doing prevent irreversible blindness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 20 publications
2
32
0
2
Order By: Relevance
“…The aetiology of the elevated IOP in obese individuals may be due to increased intra-abdominal pressure causing increased episcleral venous pressure and choroidal vascular congestion (Ece et al 2015) or increased orbital fat causing episcleral venous compression (Lam et al 2016). Stojanov et al (2013) found significantly higher mean retrobulbar adipose tissue volume in obese subjects compared to normal-weight individuals using magnetic resonance imaging.…”
Section: Discussionmentioning
confidence: 95%
“…The aetiology of the elevated IOP in obese individuals may be due to increased intra-abdominal pressure causing increased episcleral venous pressure and choroidal vascular congestion (Ece et al 2015) or increased orbital fat causing episcleral venous compression (Lam et al 2016). Stojanov et al (2013) found significantly higher mean retrobulbar adipose tissue volume in obese subjects compared to normal-weight individuals using magnetic resonance imaging.…”
Section: Discussionmentioning
confidence: 95%
“…In intraocular arteries supplying the ciliary body of the pig, NA and neuropeptide Y induced contraction that could elevate intraocular pressure, a central feature of open‐angle glaucoma (Kringelholt et al ., ). Obesity in humans, which may correlate with elevated NA signalling, is associated with both increased retrobulbar adipose tissue volume and elevated intraocular pressure (Stojanov et al ., ). A longitudinal cohort study found that hypertension was associated with (hazard ratio 1.17) increased risk of developing open‐angle glaucoma (Newman‐Casey et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Stojanov et al . [11] showed obese subjects had significantly higher IOP than subjects with normal weight. Mori et al .…”
Section: Discussionmentioning
confidence: 99%